Eliminating racial and ethnic disparities in behavioral health care in the U.S. - Hoa B. APPEL; Phuoc D. NGUYEN (Journal of Health and Social Sciences)
Notwithstanding much research and discussion about health care disparities over the years, racial and ethnic disparities persist. This is particularly evident in the Latino community where decades of research has been conducted. We propose a close examination of the three key issues in the struggle to eliminate obstacles to care: universal approach, insurance coverage, and diversifying the behavioral health care workforce. This viewpoint discusses individual and systemic barriers in the U.S., tailoring the examination to the specific needs of the specific population. Insurance coverage, especially Medicaid expansion, should be available in every state in order to allow access to all. Lastly, health care workers and providers should be prepared to treat behavioral health needs in their primary care practice. This paper highlights the need to further inve- stigate these topics in order to help eliminate the disparities that still exist in our growing populations of racial and ethnic minorities from the standpoint of health care practitioners in their practices.